Extracellular Inflammasome Particles Are Released After Marathon Running and Induce Proinflammatory Effects in Endothelial Cells - Kogel, Alexander; Fikenzer, Sven; Uhlmann, Luisa; Opitz, Lena; Kneuer, Jasmin M.; Haeusler, Karl Georg; Endres, Matthias; Kratzsch, Jürgen; Schwarz, Viktoria; Werner, Christian; Kalwa, Hermann; Gaul, Susanne; et al. (Frontiers in Physiology, 2022)
Objectives: The intracellular NLRP3 inflammasome is an important regulator of sterile inflammation. Recent data suggest that inflammasome particles can be released into the circulation. The effects of exercise on circulating extracellular apoptosis-associated speck-like protein (ASC) particles and their effects on endothelial cells are not known. Methods: We established a flow cytometric method to quantitate extracellular ASC specks in human serum. ASC specks were quantitated in 52 marathon runners 24-72 hours before, immediately after, and again 24-58 hours after the run. For mechanistic characterization, NLRP3 inflammasome particles were isolated from a stable mutant NLRP3 (p.D303N)-YFP HEK cell line and used to treat primary human coronary artery endothelial cells. Results: Athletes showed a significant increase in serum concentration of circulating ASC specks immediately after the marathon (+52 % compared to baseline, p<0.05) and a decrease during follow-up after 24- 58 hours (12 % reduction compared to immediately after the run, p<0.01). Confocal microscopy revealed that human endothelial cells can internalize extracellular NLRP3 inflammasome particles. After internalization, endothelial cells showed an inflammatory response with higher expression of the cell adhesion molecule ICAM1 (6.9-fold, p<0.05) and increased adhesion of monocytes (1.5-fold, p<0.05). Conclusion: These findings identify extracellular inflammasome particles as novel systemic mediators of cell-cell communication that are transiently increased after acute extensive exercise with high mechanical muscular load.